Adversity Quotient dan Intensi Berwirausaha pada Fresh Graduate di Yogyakarta - Senja Yulia Perwitasari; Narastri Insan Utami (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The increasing number of university graduates and limited employment opportunities have encouraged greater attention to entrepreneurship as an alternative career path. Entrepreneurial intention is influenced by various psychological factors, one of which is the Adversity Quotient, defined as an individual’s ability to withstand and overcome difficulties. This study aimed to examine the relationship between Adversity Quotient and entrepreneurial intention among recent university graduates in Yogyakarta. A quantitative approach with an associative research design was employed. The participants consisted of 134 fresh graduates aged 21–25 years who had completed their studies at universities in Yogyakarta and were selected using purposive sampling. Data were collected through Likert-scale questionnaires measuring Adversity Quotient and entrepreneurial intention. The collected data were analyzed using Pearson product–moment correlation analysis. The results revealed a very strong positive relationship between Adversity Quotient and entrepreneurial intention, with a correlation coefficient of R = 0.987 and a significance value of p < 0.05. Furthermore, the coefficient of determination (R²) was 0.974, indicating that Adversity Quotient explained 97.4% of the variance in entrepreneurial intention. The remaining 2.6% was assumed to be influenced by other factors not examined in this study, such as need for achievement, locus of control, and self-efficacy. These findings highlight the importance of developing Adversity Quotient to strengthen entrepreneurial intention among university graduates.